2016
DOI: 10.1111/ctr.12802
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic biliary neuroma after orthotopic liver transplantation: a possible cause of “unexplained” anastomotic biliary stricture

Abstract: Traumatic biliary neuromas represent a possible diagnosis for unexplained anastomotic BS after OLT. Surgical excision combined with hepaticojejunostomy is effective, allows histological diagnosis, and prevents from recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Of a cohort of 1030 consecutive patients who underwent OLT, the incidence of symptomatic TBN was 0.5%, representing 9.6% of the anastomotic biliary strictures observed. 5 Another study revealed 26 cases of hilar TBN in 93 hepatectomy specimens (27.9%) obtained between 3 and 26 months after OLT, although only a single patient (1.3%) was symptomatic. The authors found that the incidence of neuroma is higher in specimens resected more than 3 months posttransplant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of a cohort of 1030 consecutive patients who underwent OLT, the incidence of symptomatic TBN was 0.5%, representing 9.6% of the anastomotic biliary strictures observed. 5 Another study revealed 26 cases of hilar TBN in 93 hepatectomy specimens (27.9%) obtained between 3 and 26 months after OLT, although only a single patient (1.3%) was symptomatic. The authors found that the incidence of neuroma is higher in specimens resected more than 3 months posttransplant.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the move toward conservative treatment of late biliary strictures, many patients are no longer treated surgically, and a true assessment of the incidence of TBN is impossible. 5 Owing to the possibility of progression to chronic rejection and the lack of specific imaging features for a preoperative diagnosis of TBN, physicians must be mindful of the possibility of TBN when facing an unexplained anastomotic biliary stricture after OLT.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that ANs generally arise around the bile duct in the abdominal cavity [ 2 4 ]. Previous reports have demonstrated 0.5, 0.28, and 0.23% AN incidences in orthotopic liver transplantation, cholecystectomy, and biliary tract surgery, respectively [ 9 – 11 ]. Because delicate nets of nerve fibers surround the common bile duct, symptoms such as abdominal pain, pyrexia, vomiting, and jaundice commonly occur [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been described in bile ducts following biliary surgery, such as after orthotopic liver transplantation5 and cholecystectomy (both laparoscopic and open) 6 7 12. Clinically, the leading differential diagnosis typically is cholangiocarcinoma, due to the similarity of presentation, namely jaundice and intermittent symptomatic right upper quadrant pain 7.…”
Section: Traumatic Neuromamentioning
confidence: 99%